2016
DOI: 10.1038/srep24850
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigations of Optical Origins of Fluorescent Graphene Quantum Dots

Abstract: The optical properties of graphene quantum dots (GQDs) were investigated theoretically. We focused on the photoinduced charge transfer and electron-hole coherence of single-layer graphene in the electronic transitions in the visible regions. Surface functionalization with donor or acceptor groups produced a red shift in the absorption spectrum, and electrons and holes were highly delocalized. The recombination of excited, well-separated electron-hole (e–h) pairs can result in enhanced fluorescence. This fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 29 publications
2
45
0
Order By: Relevance
“…Another recently invented and attractive biomaterial from the carbon family is GQDs, which is defined as a zero-dimensional graphene sheet with a lateral dimension of less than 100 nm in one to a few layers (3–10) ( Song et al, 2015 ). During the conversion of two-dimensional graphene sheets into GQDs, the GQDs endow excellent photoluminescence due to quantum confinement ( Wang et al, 2016 ). Interestingly, as compared to other fluorescent dye or semiconductor quantum dots, the GQDs exhibit superior biocompatibility and resistance to photo-bleaching.…”
Section: Introductionmentioning
confidence: 99%
“…Another recently invented and attractive biomaterial from the carbon family is GQDs, which is defined as a zero-dimensional graphene sheet with a lateral dimension of less than 100 nm in one to a few layers (3–10) ( Song et al, 2015 ). During the conversion of two-dimensional graphene sheets into GQDs, the GQDs endow excellent photoluminescence due to quantum confinement ( Wang et al, 2016 ). Interestingly, as compared to other fluorescent dye or semiconductor quantum dots, the GQDs exhibit superior biocompatibility and resistance to photo-bleaching.…”
Section: Introductionmentioning
confidence: 99%
“…1(b,c) with top and side views; this structure includes two armchair edges and two zigzag edges with H atoms linked to the edge C atoms. A similar hexagonal honeycomb structure for graphene was introduced in our previous work 30 , 31 . The length and width of the quadrilateral graphene are 15.67 Å and 14.67 Å respectively, and the lattice constant is 1.42 Å, as shown in Fig.…”
Section: Resultsmentioning
confidence: 95%
“…The exact mechanisms of origin of GQDs photoluminescence are not yet fully understood and remain elusive as it mainly depends on synthesis processes and fabrication methods. The CVD assisted hydrophobic GQDs fluorescence properties mainly to come from photoinduced electron‐hole pairs recombination, edge effect and destruction of symmetry as we create defects and edges on the GQDs surface through prolonged sonication . As our CVD assisted GQDs are hydrophobic, soluble in organic solvents, and having alternate –C‐C‐ and –C=C‐ and there is a possible of delocalization of π‐ electrons.On the other hand, aromatic amino acids are mostly hydrophobic.On interacting with h‐GQDs, there is a hydrophobic –hydrophobic interaction of aromatic counterpart of amino acids with h‐GQDs surfaces.So, there is possible to transfer of electrons between aromatic amino acid and the h‐GQDs surfaces due to which we observed an enhancement of PL intensity.This explanation is supported by a recent report where it is shown that enhancement of graphene oxide fluorescence properties through conjugated polyelectrolytes with intramolecular charge transfer mechanism .…”
Section: Mechanismmentioning
confidence: 98%
“…It gathered tremendous interest in scientific community recently due to their unique electronic and optoelectronic properties . GQDs have largely replaced metal‐based semiconductor quantum dots due to it′s some fascinating and extraordinary properties like quantum confinement effect,edge effect, tunable photoluminescence, excellent photostability, chemical inertness, high biocompatibility, tunable band gap, low toxicity, etc. They find a wide range of applications in diverse areas like as biosensors, bioimaging, drug delivery, chemical sensing, catalysis, photovoltaics and photodynamic therapy (PDT) light emitting and environmental applications, etc.…”
Section: Introductionmentioning
confidence: 99%